Estudo de aglomerados estelares das nuvens de magalhães usando fotometria CCD na banda V - Carvalho, Luziane Oliveira (2005)
In this work we present CCD photometry in the V band for 13 star clusters in the Magellanic Clouds (LI0, L54, L59, L85, L96, NGC 1818, NGC 1866, NGC 1868, NGC 1978, NGC 2157, NGC 2213, NGC 2214, Hll). Photometric calibration has been done using standard stars from the E-regions (Graham, 1982) and the least square system GAUSSFIT (Jefferys et aI.,1988). The mean error obtained was less than 0.01 mag at a 66% confidence leveI. Cluster centers have been determinated using an implementation of the Djorgovski autocorrelation algorithm (1988) with a I" mean error. CCD frames have/ been cleaned of stellar contamination using the DAOPHOT package from IRAF, where probable non-clusters stars have been removed. We made the surface photometry in the V band and used the model considered for Elson, Fall and Freeman (1987) to fit the surface brightness curves. The clusters structural parameters, obtained from fitted brightness profiles, have been used to obtain luminosity and mass estimation for all clusters.